Heritage Tourism Trail Development in Kampung Luat, Perak: A Case Study - Jaafar, Mastura; Dahalan, Norziani; Hassan, Fatimah; Suffarruddin, Suhaida Herni (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2019)
Kampung Luat situated in Lenggong Valley, Perak, is a well-known tourist destination due to its natural attraction, archaeological elements, promotion of rural agroindustry and home-based products, as well as unwavering and strong local community commitment. Distinct local characteristics, such as traditional culture, agricultural setup, countryside landscape, and simple lifestyles, offer a different experience for its visitors. The combination of these aspects provides a huge opportunity for tourism heritage trail development. As such, this study discusses the development of a heritage trail in Kampung Luat. The initiative was taken by a group of USM researchers, along with the cooperation from the local community. Observation and focus group discussion (FGD) techniques were adopted in this study. Several meetings were conducted and the development of Kampung Luat heritage trail was proposed, which covered seven stops in four hours, which involved 20-30 residents with different roles. This heritage trail was tested by 20 respondents. The findings showed that the visitors had placed a high value in the experience and enjoyed the different rural activities, apart from proposing several suggestions for trail improvement. Low level of community readiness, lack of facilities, and communication issues were their main concerns for trail improvement. These findings suggest the implementation of stringent and effective action taken by the federal and state governments, apart from including stakeholders to both coordinate and realise the heritage trail in future to increase the competitiveness at the Lenggong Valley as a tourism destination. Keywords: Heritage trail, trail development, case study, Kampung Luat, Lenggong Valley